Research on Explosion Pressure Characteristics of Long Flame Coal Dust and the Inhibition Effect of Different Explosion Suppressants - Liu, Tianqi; Gao, Zhongyi; Xu, Yanying; Duan, Guosheng; Wang, Xiao (ACS omega, 2023)
To discuss the inhibition of long flame coal dust explosion pressure, NaHCO3, KHCO3, and NH4H2PO4 are selected as explosion suppression dust for explosion pressure tests under different conditions. The results show that when 25–38 and 38–45 μm coal dust are mixed in 1:1 ratio, the maximum explosion pressure is the largest, the maximum pressure is 0.79 MPa, and the maximum pressure rise rate is 74.89 MPa·s–1. The suppression dusts have good inhibition effect on explosion, the order of inhibition is NaHCO3, KHCO3, and NH4H2PO4 from the smallest to the largest. With the reduction of particle size of NH4H2PO4, its inhibition effect on explosion pressure is increasing, because more NH4H2PO4 particles move around coal dust particles, blocking the heat transfer and kinetic energy exchange. The above three suppression dust and their suppression methods can provide important data for dust prevention and control and have certain reference significance for carrying out explosion suppression work.